The interconnection and function of associative memory neurons are upregulated for memory strengthening - Li, Jia-Yi; Xu, Yang; Wang, Dan-Gui; Wang, Jin-Hui (Frontiers in Neural Circuits, 2023)
Memories to associated signals have been proved to rely on the recruitment of associative memory neurons that are featured by mutual synapse innervations among cross-modal cortices. Whether the consolidation of associative memory is endorsed by the upregulation of associative memory neurons in an intramodal cortex remains examined. The function and interconnection of associative memory neurons were investigated by in vivo electrophysiology and adeno-associated virus-mediated neural tracing in those mice that experienced the associative learning with pairing the whisker tactile signal and the olfactory signal. Our results show that odorant-induced whisker motion as a type of associative memories is coupled with the enhancement of whisking-induced whisker motion. In addition to some barrel cortical neurons encoding both whisker and olfactory signals, i.e., their recruitment as associative memory neurons, the synapse interconnection and spike-encoding capacity of associative memory neurons within the barrel cortex are upregulated. These upregulated alternations were partially observed in the activity-induced sensitization. In summary, associative memory is mechanistically based on the recruitment of associative memory neurons and the upregulation of their interactions in intramodal cortices.